MENGEMBANGKAN BAHASA EKSPRESIF MELALUI METODE BERCERITA (TUDI KASUS PADA ANAK USIA 4-5 TAHUN DI PAUD SPS TP KENANGA 1) - Siti Sopiah; Elnawati (Jurnal Salome : Multidisipliner Keilmuan, 2023)
The aim of this research is to document the methods used by preschool teachers at SPS TP Kenanga 1 to encourage the development of expressive language in children aged four to five years through the use of stories. The research methodology used is a case study. Teachers from Paud SPS TP Kenanga 1 participated in this research. Interviews, eyewitness accounts, and written notes are means of gathering information. Data reduction, data presentation, and drawing conclusions are the three steps of the Miles & Huberman interactive model used in this data study. This research found that in group A at PAUD SPS TP Kenanga 1, the teacher tried to help students improve their expressive language skills by inviting them to tell stories. The teacher plans the story based on the goals and themes chosen by the students, but he also provides media and materials. lots of things are happening. The teacher provides the materials needed for storytelling activities, but students are only allowed to use media that suits the needs of the class. Instead of leading with questions about the content to be presented, the instructor starts by doing a storytelling activity. Some students do not get the opportunity to participate in storytelling activities even though the teacher offers them. It is not the teacher who decides how to evaluate his or her students; rather, it is the students themselves.